Distributed differential space-time coding for two-way relay networks using analog network coding - Alabed, Samer; Pesavento, Marius; Klein, Anja (21st European Signal Processing Conference (EUSIPCO 2013), 2013)
Differential distributed space-time coding (DSTC) techniques using several transmission protocols have recently been proposed to overcome the overhead involved with the acquisition of channel state information (CSI) required for coherent processing. In this paper, a novel amplify-and-forward differential DSTC technique for two-way wireless relay networks (TWRNs) is proposed, that uses the concept of analog network coding and which does not require CSI at any node to decode the information symbols. In our transmission scheme, the relays do not waste power to transmit known information. This is achieved by combining the symbol vectors of both terminals at the relays into a single symbol vector without decoding the information symbols. Furthermore, in our scheme, the direct link between the communicating terminals can be easily incorporated to further improve the diversity gain. Simulations show a substantially improved performance in terms of bit error rate (BER) of the proposed technique as compared to the known techniques.